Digital psychiatry: concepts, framework, and implications - Wu, Hairong; Li, Ming D. (Frontiers in Psychiatry, 2025)
In this review, we consider digital psychiatry as a specialty to focus on combining the psychiatric clinical practices, psychiatric knowledge, and modern intelligent/digital approaches to automate the psychiatric clinical processes, such as diagnosis and treatment, in order to yield faster, better and consistent results, which is far beyond the development of smartphone apps, virtual reality (VR), and chatbots. Based on the recent advances in large-scale pre-trained models (PTMs), digital humans, VR and other immersive techniques, we here propose a framework to fully-automate the processes of mental health practices, and thus pave the way for digital psychiatric clinics. Specifically, in this paper, we first provide an outline of the related technical developments to digital psychiatry, by describing how digital entity, medical domain knowledge, autonomous agents and VR present new opportunities for practical clinical uses. Second, we introduce some basic mental health related issues in clinical settings, which should be considered in digital psychiatry systems. Third, we propose an outline of developing a fully-automated digital psychiatric system building on the existing artificial intelligence (AI) related technologies. Fourth, we discuss the challenges of implementing the digital psychiatry in the real-world environments. Finally, we discuss some key issues related to patients, medical providers and regulations which could not be avoided to implement the digital psychiatric systems and their applications.